Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

rebecca1233

  • 3 years ago

Solve for b. a = a+b+c/3 A.) 3A - a - c = b B.) -c / 3 = b C.) A - c / 3 = b C.) -3 - c = b

  • This Question is Closed
  1. viniterranova
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    letter A.

  2. ash2326
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    We have \[a=a+b+\frac c3\] Subtract both sides by a \[a-a=a-a+b+\frac c3\] We get \[0=0+b+\frac c3\] now subtract both sides by c/3 \[0-\frac c3=b+\frac c3-\frac c3\] we get finally \[-\frac c3=b\]

  3. viniterranova
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    a=a+b+c/3 3a-a-c=b

  4. rebecca1233
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Thank You!

  5. viniterranova
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Pass the a that is in the denominator multiplying the letter "a"

  6. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy